6C.004 Using capacity strengthening to enable effective injury prevention in Nepal. (14th March 2021) - Mytton, Julie; Ellis, Matthew; Manhandar, Sunil; Joshi, Sunil Kumar
Abstract : Context: Through a collaboration between the University of the West of England, Bristol and Kathmandu Medical College in 2017, we established the Nepal Injury Research Centre. An innovative capacity strengthening programme underpins our ethos and activities, and contributes to SDGs 17 (Capacity development) and 4 (Education). Process: Facilitated through training leads in Nepal and the UK, we provide training to eight multidisciplinary Nepali researchers with variable experience. Each leads a study/study component, thereby learning-by-doing, and has an experienced research supervisor. Researchers have an annual training needs assessment to inform support provision. Analysis: Year 2 training needs assessments reveal increasing confidence and ownership of individual training requirements. Three researchers have completed international masters level degrees with the taught component taken abroad but dissertation data collection in-country. Three have attended international short courses and two have participated in the WHO Mentor-VIP programme. Six governance/methodology workshops have taken place. Outcomes: Projects have been successfully delivered and all researchers have opportunities for oral presentations and preparing publications. The team includes Nepali nationals purely based in Kathmandu, researchers having placements overseas, and Nepali diaspora resident in the UK. This helps to dilute the traditional donor/recipient dichotomy and has facilitated a mutually supportive team. Identifying and securing PhD scholarship funding is our next challenge. Learning Outcomes: Team building can be enhanced through capacity strengthening programmes. Funding from the UK National Institute for Health Research explicitly facilitates capacity strengthening based on an established UK training model. Blurring of national boundaries is a desirable outcome of the programme.